Issues in instrumental design: The ontological problem (opportunity?) of 'liveness' for a laptop ensemble. Issue 2 (1st August 2013) - Blain, Martin
Through the recent work of Manchester Metropolitan University laptop ensemble (MMUle), 1 this article will explore issues in new instrumental design for 'live' performance. For MMUle, the intimacy of the interaction between human and machine is exposed through 'live' performance and this has resulted in the relationship between musician and machine being in a process of constant negotiation. Subsequently, this article will consider some of the technical approaches and performance strategies MMUle has developed in an attempt to better interact with technology through the design of new instruments for musical performance. It will consider the relationship between the musician and the computer as musical instrument; it will consider the causal relationship between performative action and resulting sound, which has remained an issue for some spectators of music laptop performances and will explore this in light of MMUle's approach to expand the affordance of the laptop computer in relation to its musical and performative potential; and some consideration will be given to the use of interface devices such as the computer program MaxMSP, the games controllers X-box and Wii, and the human body as MMUle attempt to interact with machines. The article will discuss some of the implications and applications of developing new software instruments for performance and this will be explored through two pathways to 'liveness': performance as a constructed 'live' event and 'liveness' considered as part of a creative strategy.